Synthesis and characterization of hydroxypropyl methylcellulose-g-poly(acrylamide)/LAPONITE® RD nanocomposites as novel magnetic- and pH-sensitive carriers for controlled drug release. Issue 55 (17th June 2015) - Mahdavinia, Gholam Reza; Ettehadi, Sanaz; Amini, Mojtaba; Sabzi, Mohammad
<x xml:space="preserve">Abstract</x> pH-responsive magnetic nanocomposite hydrogels based on hydroxypropyl methylcellulose-g-poly(acrylamide)/LAPONITE® RD (HPMC-g-PAALap) were developed.